Water Table Fluctuation in Peatlands Facilitates Fungal Proliferation, Impedes Sphagnum Growth and Accelerates Decomposition - Kim, Jinhyun; Rochefort, Line; Hogue-Hugron, Sandrine; Alqulaiti, Zuhair; Dunn, Christian; Pouliot, Remy; Jones, Timothy G.; Freeman, Chris; Kang, Hojeong (Frontiers in Earth Science, 2021)
Northern peatlands are substantial carbon sinks because organic matter in peat is highly stable due to the low rate of decomposition. Waterlogged anaerobic conditions induce accumulation of Sphagnum-derived phenolic compounds that inhibit peat organic matter decomposition, a mechanism referred to as the “enzymic latch”. Recent studies have predicted that the water table in northern peatlands may become unstable. We observed that such unstable water table levels can impede the development of Sphagnum mosses. In this study, we determined the effects of low and high frequency water table fluctuation regimes on Sphagnum growth and peat organic matter decomposition, by conducting a year-long mesocosm experiment. In addition, we conducted a molecular analysis to examine changes in abundance of fungal community which may play a key role in the decomposition of organic matter in peatlands. We found that rapid water table fluctuation inhibited the growth of Sphagnum due to fungal infection but stimulated decomposition of organic matter that may dramatically destabilize peatland carbon storage. Increased pH, induced by the fluctuation, may contribute to the enhanced activity of hydrolases in peat. We demonstrated that the water table fluctuation in peatlands impeded Sphagnum growth and accelerates decomposition due to fungal proliferation. Thus, we suggested that understanding the microbial community in the northern peatlands is essential for elucidating the possible changes in carbon cycle of peatland under the changing world.